Changing pattern of renal disease in children at pediatric nephrology clinic of a tertiary teaching hospital, Nepal: 10-year review (Journal of Patan Academy of Health Sciences, 2021)
Introduction: Children present with different renal diseases with variations according to different geographic locations. This study aims to determine the trend of pediatric renal disease presenting.Method: This retrospective study from pediatric nephrology clinic register during 2008 to May 2018 at Patan Hospital, Patan Academy of Health Sciences, Nepal to analyze the changing pattern of renal disease. The prevalence and characteristic of renal diseases were compared between the 1st and 2nd 5-y period, the age at presentation and gender was analyzed. Mean age at presentation was analyzed by independent t-test,  a p-value